Experimental Evaluation of Multiple Frost Heaving Parameters for Preflawed Granite in Beizhan Iron Mining, Xinjiang, China - Yu Wang; Dayu Long; Zulifeiya Rejuti; Huajian Wang (Geofluids)
Ice-driven mechanical weathering in cold regions is considered a main factor impacting the stability of rock mass. In this work, the response surface method (RSM) was employed to evaluate and optimize the multiple frost heaving parameters to seek the maximum frost heaving force (FHF), in combination with experimental modeling based on a specially designed frost heaving force measurement system. Three kinds of rocks were prepared with parallel flaws in it having different flaw width, length, and cementation type, and these factors were used to fit an optimal response of the maximum FHF. The experimental results reveal five distinguished stages from the frost heaving force curve, and they are inoculation stage, explosive stage, decline to steady stage, recovery stage, and sudden drop stage. The sensitivity analysis reveals the influential order of the considered factors to peak FHF, which is the rock lithology, flaw width, flaw cement type, and flaw length. For low-porosity hard rock, increasing flaw width, flaw length, and flaw cement strength can improve the probability of frost heaving failure. It is suggested that rock lithology determines the water migration ability and influences the water-ice phase transformation a lot.